Achievable Throughput-Based MAC Layer Handoff in IEEE 802.11 Wireless Local Area Networks - Wu Haitao (EURASIP Journal on Wireless Communications and Networking, 2009)
We propose a MAC layer handoff mechanism for IEEE 802.11 Wireless Local Area Networks (WLAN) to give benefit to bandwidth-greedy applications at STAs. The proposed mechanism determines an optimal AP with the maximum achievable throughput rather than the best signal condition by estimating the AP's bandwidth with a new on-the-fly measurement method, Transient Frame Capture (TFC), and predicting the actual throughput could be achieved at STAs. Since the TFC is employed based on the promiscuous mode of WLAN NIC, STAs can avoid the service degradation through the current associated AP. In addition, the proposed mechanism is a client-only solution which does not require any modification of network protocol on APs. To evaluate the performance of the proposed mechanism, we develop an analytic model to estimate reliable and accurate bandwidth of the AP and demonstrate through testbed measurement with various experimental study methods. We also validate the fairness of the proposed mechanism through simulation studies.